2017
DOI: 10.1007/s11914-017-0347-2
|View full text |Cite
|
Sign up to set email alerts
|

Current Care and Investigational Therapies in Achondroplasia

Abstract: Purpose of ReviewThe goal of this review is to evaluate the management options for achondroplasia, the most common non-lethal skeletal dysplasia. This disease is characterized by short stature and a variety of complications, some of which can be quite severe.Recent FindingsDespite several attempts to standardize care, there is still no widely accepted consensus. This is in part due to absence of concrete data on the incidence of sudden unexplained death in infants with achondroplasia and the best investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 67 publications
3
70
0
1
Order By: Relevance
“…Some of the excluded papers provide valuable information on adults with achondroplasia and important aspects of living with a skeletal dysplasia, but did not meet the inclusion criteria for the present scoping review. The most relevant papers are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the excluded papers provide valuable information on adults with achondroplasia and important aspects of living with a skeletal dysplasia, but did not meet the inclusion criteria for the present scoping review. The most relevant papers are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A number of review papers were identified, but were excluded as they were mainly concerning children or because of their non‐systematic methodology . However, we have examined their reference lists for potential eligible original papers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dominant mutations in this gene were first linked to achondroplasia (ACH; OMIM 100800), the most common form of disproportionate dwarfism in live newborns [Shiang et al, 1994;Unger et al, 2017]. Other phenotypes, such as hypochondroplasia (HCH; OMIM 146000) and thanatophoric dysplasia (TD; OMIM 187600) types I (TDI) and II (TDII) were later shown to be associated with specific mutations of that gene [Harada et al, 2009;FoldynovaTrantirkova et al, 2011].…”
mentioning
confidence: 99%